Super-resolution microscopy: Insights into mitochondria–lysosome crosstalk in health and disease - Leisten, Eric D.; Woods, Abby C.; Wong, Yvette C. (The Journal of cell biology, 2023)
Live super-resolution microscopy has allowed for new insights into recently identified mitochondria–lysosome contact sites, which mediate crosstalk between mitochondria and lysosomes, including co-regulation of Rab7 GTP hydrolysis and Drp1 GTP hydrolysis. Here, we highlight recent findings and future perspectives on this dynamic pathway and its roles in health and disease.